Efficacy and safety of radical cystectomy with ileal conduit for muscle-invasive bladder cancer in the elderly: a multicenter retrospective study - Zhang, Heqian; Li, Anrui; Wang, Wentao; Xu, Songlin; Li, Changfu; Teng, Lichen (Frontiers in Oncology, 2024)
Objective: Radical cystectomy with ileal conduit is the current mainstay of treatment for muscle-invasive bladder cancer and is also a high-risk procedure. Existing studies have limited targeted assessment of the efficacy and safety of this procedure, and the patient population appropriate for this procedure is still poorly defined. We sought to longitudinally analyze differences in the efficacy and safety of radical cystectomy with ileal conduit by age subgroups to assess whether the age factor should be used as an exclusion criterion when selecting this procedure.: We retrospectively examined the clinicopathological data of patients with MIBC treated with RC with IC at the Cancer Hospital of Harbin Medical University between February 2014 and October 2023. Additionally, we utilized clinical and pathological data from the SEER database (2000-2020) for external validation of our findings. Patients were categorized into elderly (≥70 years at diagnosis) and non-elderly (<70 years) groups. Statistical analyses included t-tests,non-parametric tests for continuous data, chi-square tests for categorical data, and Kaplan-Meier survival analysis.Results: In this study, 152 patients were included: 119 were categorized as non-elderly and 33 as elderly. For external validation, data from 416 patients in the SEER database were analyzed, with 172 classified as non-elderly and 244 as elderly. The results indicated that elderly patients were more likely to require ICU transfer postoperatively but exhibited a lower incidence of stoma inflammation. Additionally, both the data from our center and the external validation from the SEER database showed a concordance in cancer-specific survival (CSS) between the elderly and non-elderly groups. The efficacy of RC with IC was comparable in both elderly and non-elderly patients.For longitudinal age subgroups, RC with IC for both elderly and non-elderly MIBC had good efficacy and safety, and good quality of life after surgery. Although there are surgical and perioperative risks in elderly patients, there is no significant difference compared with non-elderly patients. In elderly patients requiring RC for bladder cancer, IC should remain the preferred mode of urinary diversion, and old age should not be used as an absolute exclusion criterion for IC.